Activation Independent Functions of Collagen Receptor Integrins alpha1beta1 and alpha2beta1 - Salmela, Maria (fi=Turun yliopisto|en=University of Turku|, 2017)
Cell adhesion to extracellular matrix (ECM) molecules, such as collagen, is mediated by the integrin family of cell surface receptors. Integrins are also exploited by several viruses during cell entry. Integrins literally integrate the ECM to the cytoskeleton by binding ECM ligands with their large head domain, and by connecting to the cytoskeleton through various focal adhesion proteins that bind integrin tails. Integrin tails recruit over 200 focal adhesion proteins to mediate cellular signaling events to control adhesion dependent cell growth and cell movement. Aberrant integrin signaling can lead to uncontrolled cell growth, which in turn can induce cancer and metastases. The affinity of integrins to their ligands, as well as interactions between integrin tails and focal adhesion proteins, are controlled by integrin activity and clustering. Integrins undergo conformational activation from a bent to primed/extended and finally to a fully active conformation. Integrin priming facilitates ligand binding, and ligand interactions further induce full activation through the separation of integrin legs, promoting protein recruitment to focal adhesions and integrin clustering. The bent integrin conformation has been considered nonfunctional, since the ligand binding domain faces the cell membrane and ligand interactions are thus mostly prevented. However, in this thesis work echovirus 1 was shown to interact specifically with the bent conformation of alpha2beta1-integrins (I). Furthermore, it was shown that under flow conditions platelet alpha2beta-integrins can bind to collagen without receptor priming (III). The recruitment of focal adhesion proteins and the initiation of integrin signaling have been thought to require integrin conformational activation. Here, using echovirus 1 as a model system, I demonstrate that clustered alpha2beta1-integrins can mediate Focal Adhesion Kinase signaling without conformational activation of the integrin (II). Integrins are controlled not only by regulating their conformational activity and clustering but also by influencing their expression levels and the pool on the cell surface. A fourth level of regulation occurs at focal adhesions where integrins are connected to the cytoskeleton. In my thesis I show that during cell spreading the reduced recruitment of the cytoskeleton protein vimentin to focal adhesions induces the formation of lamellipodia independently of alpha1beta1-integrin conformational activation (IV). I also show that 1-integrin-mediated cell adhesion can be prevented without affecting the activity or surface expression of the integrin (V). In conclusion, this thesis emphasizes the importance of the nonactivated integrin conformation in regulating cell adhesion, and demonstrates that integrin mediated functions are regulated at several levels